DC and AC Characteristics of GaAs/InGaAs/AIGaAS Real Space Transfer Transistors - H. C. Chen (Active and Passive Electronic Components)
DC and AC performances of a GaAs/InGaAs/AIGaAs negative resistance field-effect transistor (NERFET) are demonstrated by molecular beam epitaxy (MBE) for the first time. The negative differential resistance (NDR) resulted from the observation of the hot electron real space transfer effect in InGaAs channel. By Hall measurements, the structure shows carrier mobility as high as 4300 (13500) cm2/v-s at 300 (77)K, which is suitable for high frequency operation. For DC performance, the largest peak-to-valley current ratio of the device is about 5 at room temperature. For AC performance, S-parameter measurements of high frequency and microwave characteristics indicate a projected maximum frequency of oscillation of fmax⁡=2.7GHz and a current gain cutoff frequency (fT) occurs at 1.8GHz.